Protest und Selbstbeschreibung: Selbstbezüglichkeit und Umweltverhältnisse sozialer Bewegungen - Tratschin, Luca (transcript, 2016)
This volume shows how social movements develop through the extremely selective interpretation and recontextualisation of individual protests.